Observation of two new Ξ-b baryon resonances - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physical review letters, 2015)
Two structures are observed close to the kinematic threshold in the Ξ0bπ− mass spectrum in a sample of proton-proton collision data, corresponding to an integrated luminosity of 3.0 fb−1, recorded by the LHCb experiment. In the quark model, two baryonic resonances with quark content bds are expected in this mass region: the spin-parity JP=(1/2)+ and JP=(3/2)+ states, denoted Ξ'−b and Ξ*−b. Interpreting the structures as these resonances, we measure the mass differences and the width of the heavier state to be m(Ξ'−b)−m(Ξ0b)−m(π−)=3.653±0.018±0.006 MeV/c2, m(Ξ*−b)−m(Ξ0b)−m(π−)=23.96±0.12±0.06 MeV/c2, Γ(Ξ*−b)=1.65±0.31±0.10 MeV, where the first and second uncertainties are statistical and systematic, respectively. The width of the lighter state is consistent with zero, and we place an upper limit of Γ(Ξ'−b)<0.08 MeV at 95% confidence level. Relative production rates of these states are also reported.